Under-replicated DNA: The byproduct of large genomes? - Bertolin, Agustina Paola (2020)
In this review, we provide an overview of how proliferating eukaryotic cells overcome one of the main threats to genome stability: incomplete genomic DNA replication during S phase. We discuss why it is currently accepted that double fork stalling (DFS) events are unavoidable events in higher eukaryotes with large genomes and which responses have evolved to cope with its main consequence: the presence of under-replicated DNA (UR-DNA) outside S phase. Particular emphasis is placed on the processes that constrain the detrimental effects of UR-DNA. We discuss how mitotic DNA synthesis (MiDAS), mitotic end joining events and 53BP1 nuclear bodies (53BP1NBs) deal with such specific S phase DNA replication remnants during the subsequent phases of the cell cycle.